National guidance for adapting to coastal hazards and sea-level rise: Anticipating change, when and how to change pathway. Issue 82 (April 2018) - Lawrence, Judy; Bell, Rob; Blackett, Paula; Stephens, Scott; Allan, Sylvia
Highlights: Sea-level rise is a decision-makers challenge. National guidance integrates ability for future adjustments. Future risk entrenchment can be avoided. Dynamic Adaptive Pathways Planning is used for managing uncertainty. Community values and monitoring can be based on decision triggers. Abstract: Sea-level rise challenges public policy-making because existing planning frameworks and methods are designed to promote certainty using static and time-bound planning and legal instruments. Sea-level rise is a dynamic and uncertain process, which is deeply uncertain towards the latter part of this century and beyond. Communities require decision making approaches that can enable adjustments to policies ahead of damage, without entrenching current exposure to hazards or incurring larger than necessary adjustment costs in the future. We first discuss the nature of the sea-level problem, the policy context that creates decision-making challenges and how they have been typically addressed through policy and practice. Secondly, we show how an assessment and planning approach, designed to address uncertainty and change (the Dynamic Adaptive Policy Pathways (DAPP) planning approach), has been integrated into national guidance for coastal hazard and climate change decision-making in New Zealand. The Guidance integrates hazard and sea-level rise assessments with uncertainty type and with the scale and scope of activity. It is underpinned with values-based community engagement, and uses signals and decision triggers for monitoring and adjusting pathways to meet objectives over time. The applicability of the approach in the Guidance for other policy problems involving uncertainty, is also discussed.